2020
DOI: 10.1097/md.0000000000021414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of agoraphobia in patients with panic disorder

Abstract: Agoraphobia is frequently accompanied by panic disorder and causes considerable suffering. The aim of this study was to compare clinical features and treatment courses between patients with and without agoraphobia in panic disorder. In this retrospective study, 87 patients with panic disorder were divided into two groups depending on the presence of agoraphobia: patients with agoraphobia (PDA, n = 41) and patients without agoraphobia (PD, n = 46). Agoraphobia subscale score of the Albany Panic and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…PD patients with comorbid agoraphobia were more likely to emerge serious anxiety symptom and avoidance behavior, and agoraphobia was considered to result from recurrent panic attacks ( 54 ). A recent study also showed that patients with PDA (panic disorder with agoraphobia) had severer anxiety symptom and higher anxiety trait than those with PD alone ( 55 ). PDA patients were reported greater self-criticism and fatalism ( 56 ) and higher severity of fear of bodily sensation ( 57 ) than those with PD alone.…”
Section: Discussionmentioning
confidence: 99%
“…PD patients with comorbid agoraphobia were more likely to emerge serious anxiety symptom and avoidance behavior, and agoraphobia was considered to result from recurrent panic attacks ( 54 ). A recent study also showed that patients with PDA (panic disorder with agoraphobia) had severer anxiety symptom and higher anxiety trait than those with PD alone ( 55 ). PDA patients were reported greater self-criticism and fatalism ( 56 ) and higher severity of fear of bodily sensation ( 57 ) than those with PD alone.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with prior studies, which demonstrated that clinical characteristics worsen when agoraphobia and PD are comorbid. 6 40 However, some points should be considered when interpreting KSCL95 findings: because KSCL95 comprehensively evaluates various psychiatric symptoms through a single self-report questionnaire (multidimensional instrument), it is necessary to exercise caution in determining which specific features show a significant group difference. 41 Further studies using individual scales for each feature are needed to validate the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…1 More than half of diagnosed PD cases are accompanied by agoraphobia 2 3 : a fear of open or crowded situations, such as public transportation, due to the possibility of experiencing panic-like symptoms with no options for receiving help or escaping. 1 Compared with patients with PD alone, patients with PD and comorbid agoraphobia show an extended illness duration, 4 more frequent comorbidities, 5 more severe panic attacks, and higher levels of emotional symptoms, including depression, 6 indicating that PD with comorbid agoraphobia has a more severe clinical presentation than PD alone.…”
Section: Introductionmentioning
confidence: 99%
“…Agoraphobia, which can be diagnosed alone but is typically accompanied by panic disorder, is a clinical condition associated with poor prognosis in the treatment of panic disorder. 48 Comorbid bipolar disorder is also regarded as a poor prognostic factor for the treatment of panic disorder. 49 In the three cases above, two patients (cases 1 and 3) had suffered panic disorder with agoraphobia for a long period of time, and none of the patients responded to two or three consecutive trials of pharmacotherapy, including quetiapine combined with valproate (cases 1 and 2) and quetiapine combined with lithium (case 3).…”
Section: Discussionmentioning
confidence: 99%